Functional Gain After Inpatient Stroke Rehabilitation. Issue 10 (October 2015) - Scrutinio, Domenico; Monitillo, Vincenzo; Guida, Pietro; Nardulli, Roberto; Multari, Vincenzo; Monitillo, Francesco; Calabrese, Gianluigi; Fiore, Pietro
<x xml:space="preserve">Abstract</x> Background and Purpose— Prediction of functional outcome after stroke rehabilitation (SR) is a growing field of interest. The association between SR and survival still remains elusive. We sought to investigate the factors associated with functional outcome after SR and whether the magnitude of functional improvement achieved with rehabilitation is associated with long-term mortality risk. Methods— The study population consisted of 722 patients admitted for SR within 90 days of stroke onset, with an admission functional independence measure (FIM) score of <80 points. We used univariable and multivariable linear regression analyses to assess the association between baseline variables and FIM gain and univariable and multivariable Cox analyses to assess the association of FIM gain with long-term mortality. Results— Age (P<0.001), marital status (P=0.003), time from stroke onset to rehabilitation admission (P<0.001), National Institutes of Health Stroke Scale score at rehabilitation admission (P<0.001), and aphasia (P=0.021) were independently associated with FIM gain. The R2 of the model was 0.275. During a median follow-up of 6.17 years, 36.9% of the patients died. At multivariable Cox analysis, age (P<0.0001), coronary heart disease (P=0.018), atrial fibrillation (P=0.042), total cholesterol (P=0.015), and total FIM gain (P<0.0001) were independently associated with mortality. The adjusted hazard ratio for death significantly decreased across tertiles of increasing FIM gain. Conclusions— Several factors are independently associated with functional gain after SR. Our findings strongly suggest that the magnitude of functional improvement is a powerful predictor of long-term mortality in patients admitted for SR.